FC038: Efficacy of Levamisole for Maintaining Remission after the First Flare of Steroid Sensitive Nephrotic Syndrome in Children: The Nephrovir-3 Randomized Controlled Trial. (3rd May 2022) - Dossier, Claire; Kwon, Theresa; Nekrouf, Celia; Bensaid, Philippe; Parmentier, Cyrielle; Galerne, Aurelien; Chace, Anne; Gobet, Sophie; Nathanson, Sylvie; Mahdi, Fouad; Zenkhri, Ferielle; Rouget, Sebastien; et al.
Abstract: BACKGROUND AND AIMS: In children with Steroid Sensitive Nephrotic Syndrome (SSNS), relapse after the first flare occurs in 80% of cases, whatever the dosage or duration of initial steroid therapy. Therefore, there is an unmet need for early interventions to reduce the incidence of relapse and subsequent steroids and immunosuppressive drug exposure. Levamisole is an antihelmintic drug with an immunomodulatory action that reduces relapses in children with frequent relapses or steroid-dependant NS. NEPHROVIR-3 is the first trial to assess the efficacy of levamisole in increasing duration of initial remission after the diagnosis of INS. METHOD: NEPHROVIR-3 is a multicentric placebo-controlled randomized trial (1:1), in 38 centres of the Paris area, France. Patients were included at INS diagnosis and randomized, when steroid sensitive within 4 weeks, to receive either levamisole 2.5 mg/kg/48 h or placebo for 6 months, in addition to the French steroid protocol (18 weeks-3990 mg/m 2 ). Primary outcome was the relapse-free survival at 1 year. The effect of the study drug was analysed by a Cox proportional hazard model stratified on centre. RESULTS: Between September 2017 and February 2020, 86 patients were included, median age at INS onset was 5 years (IQ 3–7), with 69% of boys. At 4 weeks, 68 of them were randomized. Median time to remission was 8.5 days (IQ 6–12). Relapse-free survival at 12 months was 53.8% [95 confidence interval (95% CI) 34.7–69.5] in the levamisole group versus 20.9% (7.2–39.4) in the placebo group ( P = .007). The risk of relapse associated with levamisole was HR = 0.37 (95% CI 0.15–0.89). CONCLUSION: Early treatment with levamisole at the first flare of childhood SSNS significantly improves relapse-free survival at 1 year.